Biodiesel synthesis from Ceiba pentandra oil by microwave irradiation-assisted transesterification: ELM modeling and optimization - Silitonga A.S.; Shamsuddin A.H.; Mahlia T.M.I.; Milano J.; Kusumo F.; Siswantoro J.; Dharma S.; Sebayang A.H.; Masjuki H.H.; Ong H.C. (Elsevier Ltd, 2023)
Alternative fuels; Energy efficiency; Irradiation; Knowledge acquisition; Learning algorithms; Machine learning; Microwave irradiation; Optimization; Potassium hydroxide; Synthetic fuels; Transesterification; Biodiesel production; Catalyst concentration; Cuckoo search algorithms; Extreme learning machine; Modeling and optimization; Research and development; Transesterification process; Virtual experimentations; Biodiesel; angiosperm; biofuel; catalyst; hydroxide; irradiation; microwave radiation; optimization; Ceiba pentandra